2009
DOI: 10.1111/j.1748-5967.2009.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Ca2+ ion as modulators in cellular immunity of the Sunn pest Eurygaster integriceps Puton (Heteroptera: Scutelleridae)

Abstract: Environmental conditions in addition to divalent cations may affect the interactions between pathogens and insects. Elucidation of factors which modulate insect immune responses could be a significant part of investigations in this area. In this study, adults of Eurygaster integriceps, as the destructive pest of wheat, were kept at different temperatures in addition to injection with different concentrations of Ca2+ to find the effect on cellular immune reactions against Beauveria bassiana. Results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It is reported that divalent cations enhance or are required for phagocytosis, nodule formation, encapsulation, and other immune-related processes in insects (Zibaee et al, 2009). The effect of metal ions on PO has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that divalent cations enhance or are required for phagocytosis, nodule formation, encapsulation, and other immune-related processes in insects (Zibaee et al, 2009). The effect of metal ions on PO has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental temperature has been shown to affect positively the amount of PO in T. molitor being higher at 30°C than at 20 or 10°C (Catalán et al, 2012), while PO activity in Eurygaster integriceps was higher and more persistent in time at 40°C (over 72 h) than at 20 or 30°C (Zibaee et al, 2009). Moreover, field studies have confirmed that environmental temperature is positively correlated with PO activity (Fuller et al, 2011).…”
Section: Discussionmentioning
confidence: 83%
“…Previous results indicate that immune response of insects is affected by environmental temperature (Ouedraogo et al 2003, Zibaee et al 2009, Rolff & Reynolds 2009, Adamo & Lovett 2011. Par ticularly, the constitutive immune response seems to be highly sensitive to thermal conditions, being higher at elevated temperatures (Catalán et al 2012).…”
Section: Discussionmentioning
confidence: 99%